1969
DOI: 10.1113/jphysiol.1969.sp008802
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic responses demonstrating the extracellular character of the sarcoplasmic reticulum

Abstract: SUMMARY1. Changes in the dimensions of the sarcoplasmic reticulum in frog sartorius muscles exposed to hypertonic and hypotonic solutions have been studied with the electron microscope.2. The volume of the sarcoplasmic reticulum has been found to be linearly related with a negative slope to the reciprocal of the osmotic pressure. Over the range 075 to 3-5 x normal osmotic pressure the reticulum volume has been calculated to change from 11x5 to 18-5 % of normal cell volume.3. These changes in sarcoplasmic retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

1969
1969
1984
1984

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…On the basis of the assmnptioii that the rapidly exchanging compartment contained Na"* at extracellular concentrations, Rogus and Zierler (1973) determined its volume to be about 14% of fibre volume, suggesting tliat it was the intra-fibre extracellular compartment proposed by previous workers. The volume behaviour of the rapidly exchanging compartment in muscles exposed to anisotonie solutions was consistent with the predicted o.smotic behaviour of the intra-fibre extracellular compartment and virtually identical with the observed volume of the sarcoplasmie rcticulum in Birks and Davey's (1969) fixed material.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…On the basis of the assmnptioii that the rapidly exchanging compartment contained Na"* at extracellular concentrations, Rogus and Zierler (1973) determined its volume to be about 14% of fibre volume, suggesting tliat it was the intra-fibre extracellular compartment proposed by previous workers. The volume behaviour of the rapidly exchanging compartment in muscles exposed to anisotonie solutions was consistent with the predicted o.smotic behaviour of the intra-fibre extracellular compartment and virtually identical with the observed volume of the sarcoplasmie rcticulum in Birks and Davey's (1969) fixed material.…”
Section: Introductionsupporting
confidence: 82%
“…If Birks and Davey's (1969) results are artefactual, then rejection of Biiks' (1965) hypothesis must be seriously cousidered. Such rejection would be in accord with the observation that the sarcoplasniic reticulum of frog muscle, fixed by the freezing technique mentioned above and analyzed using an electron probe, does not appear to contaiu atomic sodium aud chlorine at their extracellular ionic c(jncentrations (Somlyo et al, 1977).…”
Section: Sarroplasmic Reticulummentioning
confidence: 99%
“…There is little direct evidence available which would allow us to identify the slow compartment with the sarcoplasmic reticulum. However system and sarcoplasmic reticulum does not seem improbable, as it would appear that much larger molecules such as sucrose (Birks & Davey, 1969), ruthenium red (Luft, 1971;Dulhunty & Gage, 1973) and silver salts (Baker, 1965) can enter the sarcoplasmic reticulum in this way. In glycerol-loaded fibres transferred to Ringer solution, glycerol would rapidly diffuse out of the transverse tubules.…”
Section: Discussionmentioning
confidence: 99%
“…The excitation process, which begins at the muscle fibre surface, evidently reaches the myofibrils by a route along the transverse tubular system (Huxley & Taylor, 1958). But after the sarcolemma has been removed from a muscle fibre, graded or 'all-or-none' activation can also be produced, apparently by depolarization of some element of the internal membrane system which is electrically continuous longitudinally over many sarcomeres (Costantin & Podolsky, 1967; also see Birks & Davey, 1969). Our experiments have shown that a prolonged stimulus inhibits the spread of activation throughout a muscle fibre (Pls.…”
Section: Discussionmentioning
confidence: 99%